2015
DOI: 10.1590/1807-3107bor-2015.vol29.0126
|View full text |Cite
|
Sign up to set email alerts
|

Caries-risk profiles in Italian adults using computer caries assessment system and ICDAS

Abstract: The aim of this study was to examine the correlation among socio-behavioral factors, caries status and caries risk, calculated through Cariogram, in an adult population. Four hundred eighty subjects (mean age 40.73, SE ± 0.33) randomly selected from the municipal electoral registry consented to participate in the survey. Subjects were examined, and the International Caries Detection Assessment System (ICDAS) index was registered. A highly structured questionnaire was submitted to investigate (1) personal data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 21 publications
8
21
0
Order By: Relevance
“…Oscarson et al [2017] reported that of Norwegian 35-to 49-year-old adults, 40% had dentin caries lesions and 70% had caries lesions of any stage. In a study on Italian adults, on average 60% had caries lesions, and initial lesions were less common than dentin lesions [Carta et al, 2015]. The prevalence of dentin caries lesions in this study population (40%) is in line with previous studies on Finnish adults and in Nordic countries [Oscarson et al, 2017].…”
Section: Discussionsupporting
confidence: 90%
“…Oscarson et al [2017] reported that of Norwegian 35-to 49-year-old adults, 40% had dentin caries lesions and 70% had caries lesions of any stage. In a study on Italian adults, on average 60% had caries lesions, and initial lesions were less common than dentin lesions [Carta et al, 2015]. The prevalence of dentin caries lesions in this study population (40%) is in line with previous studies on Finnish adults and in Nordic countries [Oscarson et al, 2017].…”
Section: Discussionsupporting
confidence: 90%
“…Although fewer in number compared to the child population, some researchers have accessed caries using ICDAS in clinical and epidemiological studies involving adults (15,16). To our knowledge, no study has brought this aspect of comparison to epidemiological studies of the adult population, which should also have the diagnosis of caries and its treatment based on the philosophy of minimal intervention.…”
Section: Introdutionmentioning
confidence: 99%
“…For example, nine different caries surfaces measures and seven caries teeth measures were identified in this review. Some studies grouped them to classify caries as dentin and enamel lesions while others classified them as initial/early, moderate/established and severe/extensive lesions . In addition, some studies combined all scores of caries into one group .…”
Section: Discussionmentioning
confidence: 99%